Three-dimensional comparison of digital models obtained from different types of scanning devices - Santos, Lucas Gonçalves (2025)
This study aimed to compare individual tooth changes between three different types of scanning devices using three-dimensional superimposition of digital dental models. This retrospective study included digital dental models of 20 adults (12 female, 8 male; mean age of 31.8 ± 5.52 years) with acceptable occlusion obtained directly from a Trios® intraoral scanner (T) and Panda® intraoral scanner (P), and indirectly from a E3® desktop (E). Landmarks were placed bilaterally in central incisors, canines, first premolars and first molars in the maxilla and mandible to perform the superimpositions using 3D Slicer software. Three-dimensional displacements were quantified. Mean differences and standard deviation were obtained for all variables. Intergroup comparison was performed using repeated measurers ANOVA, followed by Tukey test or Friedman test followed by Durbin-Conover test (p<0.05). In the maxilla, similar results were obtained for the three equipment. Negligible discrepancies were observed, with a minor variation in central incisors between T and E scans (MD: -0.07 ± 0.21; p=0.012). Greater discrepancies were observed for the mandibular arch, especially when assessing digital models obtained indirectly from the conventional plaster models. Mandibular digital dental models derived from plaster models demonstrated greater discrepancies in comparison with other scanning devices, whereas maxillary dental models were similar across different equipment. Intraoral scanners produced similar digital dental models.